Housework share between partners: Experimental evidence on gender identity - Katrin Ausprung; Maria Iacovou; Cheti Nicoletti (University of Essex, Institute for Social and Economic Research (ISER), 2015)
Using an experimental design, we investigate the reasons behind the gendered division of housework within couples. In particular, we assess whether the fact that women do more housework than men may be explained by differences in preferences deriving from differences in gender identity between men and women. We find little evidence of any systematic gender differences in the preference for housework, suggesting that the reasons for the gendered division of housework lie elsewhere.
Keywords: D10; J16; J22; 330; gender; housework; unpaid work; division of labor; experiment